2018
DOI: 10.3847/1538-3881/aad549
|View full text |Cite
|
Sign up to set email alerts
|

Coma Morphology, Numerical Modeling, and Production Rates for Comet C/Lulin (2007 N3)

Abstract: We report on narrowband photometry and extensive imaging observations of comet C/Lulin (2007 N3) obtained at Lowell Observatory during 2008 and 2009. Enhanced CN images revealed a double corkscrew morphology with two near-polar jets oriented approximately east-west, and both CN and dust images showed nightly rotational variability and seasonal changes in bulk morphology. We determined a rotational pole direction of RA/Dec = 81°/+29° with an obliquity of 97°, and a sidereal rotation period of 41.45 ± 0.05 hr.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 29 publications
1
10
0
Order By: Relevance
“…Furthermore, NH, C 2 , and C 3 suffer dust contamination that required photometric conditions in order to be properly analyzed, and such calibrations were too time consuming except on our dedicated nights. We made a programmatic decision to prioritize regular CN monitoring from December onwards so that we could tightly constrain the rotation period at as many epochs as possible to look for a changing rotation period; this strategy has proven to be very successful in the past, e.g., for C/2004 Q2 Machholz (Farnham et al 2007), C/2007 N3 Lulin (Bair et al 2018), 103P/Hartley 2 (Knight & Schleicher 2011;Samarasinha et al 2011), and 41P/Tuttle-Giacobini-Kresák (Schleicher et al 2019). The CN imaging was the focus of Paper I; below we concentrate on the morphology and behavior of the dust and the remaining gas species.…”
Section: Imaging Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, NH, C 2 , and C 3 suffer dust contamination that required photometric conditions in order to be properly analyzed, and such calibrations were too time consuming except on our dedicated nights. We made a programmatic decision to prioritize regular CN monitoring from December onwards so that we could tightly constrain the rotation period at as many epochs as possible to look for a changing rotation period; this strategy has proven to be very successful in the past, e.g., for C/2004 Q2 Machholz (Farnham et al 2007), C/2007 N3 Lulin (Bair et al 2018), 103P/Hartley 2 (Knight & Schleicher 2011;Samarasinha et al 2011), and 41P/Tuttle-Giacobini-Kresák (Schleicher et al 2019). The CN imaging was the focus of Paper I; below we concentrate on the morphology and behavior of the dust and the remaining gas species.…”
Section: Imaging Resultsmentioning
confidence: 99%
“…On the other hand, we have generally assumed that such features are not seen, in part, because the dust has low ejection velocities and large velocity dispersions, requiring excellent spatial resolution to be identified. We have also frequently seen approximately stationary sunwardfacing features in some comets, e.g., C/2007 N3 Lulin (Bair et al 2018), 41P/Tuttle-Giacobini-Kresák (Bair et al 2018;Schleicher et al 2019), yet such features are absent in Wirtanen. Wirtanen's historically close apparition should have made the identification of any such features far easier than in most comets.…”
Section: Dust Morphology and Behaviormentioning
confidence: 89%
See 2 more Smart Citations
“…As expected, light from the nucleus itself could not be separated from that from the inner coma and a nuclear lightcurve could not be measured. Our primary goal was therefore detection and analyses of gas and/or dust jets, similar to what we have done on several other comets, including Hyakutake (C/1996 B2;Schleicher & Woodney 2003), Lulin (C/2007 N3; Bair et al 2018), 103P/Hartley 2 (Knight & Schleicher 2011, and 10P/Tempel 2 (Knight et al 2012). Going into the apparition, we considered it very likely that T-G-K would have one or more distinctive jets since jets require isolated source regions and the comet's relatively low activity level suggested that much of the surface of the nucleus was inert.…”
Section: Introductionmentioning
confidence: 99%